POLTEXT - Données textuelles pour l'analyse des politiques du Canada - U Laval
Keywords: _open access

Indian Affairs Annual Reports, 1864-1990 - Canada, Library and Archives (2022)
This database includes annual reports from the Department of Indian Affairs and Northern Development and its predecessors from 1864 to 1990. The reports in this database have been digitized, transcribed, and can be viewed online.
Last Modified: 2023-01-11
Keywords: _open access

Publications gouvernementales - Canadiana
Find publications on a broad range of topics relating to indigenous rights, labour, justice, arts and literature, and the military.
Keywords: _open access

Ressources parlementaires historiques canadiennes - Bibliothèque du Parlement
Base de données qui contient les versions numérisées des publications parlementaires depuis la 1re session de la 1re législature (1867) jusqu’au début de leur diffusion sur noscommunes.ca et sencanada.ca.
Keywords: _open access

Parlinfo - Parlement du Canada
de 1867 à nos jours. People, Parliament, Departments and Committees, Political Parties, Legislation, Elections and Ridings.
Keywords: _open access

Débats parlementaires et Journaux (Chambre des communes ou Sénat)
voir les sections correspondantes
Keywords: _open access

Édits, ordonnances royaux, déclarations et arrêts du Conseil d'État du roi, concernant le Canada
Sir Robert Shore Milnes (1801)
Keywords: _open access

Débats parlementaires Québec
voir la section « Débats parlementaires » du guide
Keywords: _open access